Case Report: A Case of Locally Advanced Pancreatic Cancer Which Achieved Progression Free for Over 12 Months by Subsequent Therapy with Anlotinib Hydrochloride Plus Tegafur-Gimeracil-Oteracil Potassium (TS-1) - Luo, Dongcheng; Liao, Sina; Li, Qian; Lin, Youzhi; Wei, Junbao; Li, Yongqiang; Liao, Xiaoli (Frontiers in Oncology, 2022)
Pancreatic cancer is a malignant tumor with a very poor prognosis. It can be called the "most destructive of all cancers" and is irresponsive to systemic therapy. Several studies have shown that Tegafur-Gimeracil-Oteracil Potassium (hereinafter referred to as TS-1) is no less superior to Gemcitabine in the treatment of advanced pancreatic cancer. A number of current clinical studies have shown that targeted therapy combined with chemotherapy reflects therapeutic advantages in pancreatic cancer. In vitro and in vivo experiments have also demonstrated that Anlotinib can curb the proliferation of pancreatic cancer cells and induce their apoptosis. Here, we report for the first time a patient with locally advanced pancreatic cancer who was switched to Abraxane combined with Gemcitabine (AG regimen) chemotherapy after the progression with chemo-radiotherapy. However, the disease still rapidly progressed without control. It then was switched to TS-1 chemotherapy combined with Anlotinib targeted therapy and achieved good efficacy. In this case, the patient achieved progression-free survival (PFS) of greater than 14 months using Anlotinib targeted therapy combined with TS-1 chemotherapy. At present, the progress of the disease is stopped and the general condition of the patient is good while the targeted therapy and chemotherapy by oral administration is still in progress. This suggests that patients with advanced pancreatic cancer may benefit from treatment with the Anlotinib targeted therapy combined with TS-1 chemotherapy.